Liquid Crystal Modified Polylactic Acid Improves Cytocompatibility and M2 Polarization of Macrophages to Promote Osteogenesis - Zheng, Zexiang; Wang, Renqin; Lin, Jianjun; Tian, Jinhuan; Zhou, Changren; Li, Na; Li, Lihua (Frontiers in Bioengineering and Biotechnology, 2022)
Liquid crystalline phases (LC phases) widely present in organism. The well-aligned domain and liquidity in LC phases are necessary for various biological functions. How to maintain the stable of LC phase in biological applications and release the superior biology of them is still under pondering. In this work, a series of composite films (PLLA/LC) were prepared using cholesteryl oleyl carbonate (COC), cholesteryl pelargonate (CP) and polylactic acid (PLLA) via controlled facile one-pot approach. The results showed that the thermo-responsive PLLA/LC films exhibited stable LC phases at human body temperature and the cytocompatibility of PLLA was improved significantly after modified by LC. In addition, the M2 polarization of macrophages (RAW264.7) was enhanced in PLLA/LC films and the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) were improved while co-cultured with macrophages. The bone regeneration in vivo of the materials was verified by calvaria repair, in which the amount of new bone in PLLA-30%LC group greater than that in PLLA group. This work revealed that the liquid crystal modified PLLA could promote osteogenesis through immunomodulation.